Magnification of the input impedance of a magnetizing winding by electronic means - Sankaran, P.; Kumar, V.J.; Murugarasu, S. (2001)
The problem of reducing the exciting current drawn by a winding for establishing flux in a magnetic core has been receiving considerable attention over the years. Conventionally, quality materials of high permeability and low loss have been employed for this purpose. The 'two-stage' principle has also been applied along with buffer amplifiers for increasing the input impedance, especially of inductive voltage dividers. In this paper, we propose an alternative electronic feedback compensation technique employing an i-to-i converter for achieving the above goal in both single-core and two-stage arrangements. A quantitative analysis of the circuit is presented to determine the factor of improvement attainable in the two cases. Experimental results on a model, two-core arrangement are provided, to establish the feasibility of the proposed technique.